Alternating Intramolecular and Intermolecular Catalyst‐Transfer Suzuki–Miyaura Condensation Polymerization: Synthesis of Boronate‐Terminated π‐Conjugated Polymers Using Excess Dibromo Monomers. Issue 1 (28th October 2015) - Nojima, Masataka; Kosaka, Kentaro; Kato, Masaru; Ohta, Yoshihiro; Yokozawa, Tsutomu
Abstract : The Suzuki–Miyaura coupling polymerization of dibromoarene1 and arylenediboronic acid (ester)2 with a Pd catalyst having a high propensity for intramolecular catalyst transfer is reported. The polymerization of excess1 with2 affords high‐molecular‐weight π‐conjugated polymer having boronic acid (ester) moieties at both ends, contrary to Flory's principle. This unstoichiometric polycondensation behavior is accounted for by intramolecular transfer of the Pd catalyst on1 . In the polymerization of1 and2 having different aryl residues, high‐molecular‐weight polymer is obtained when the stronger donor aromatic is used as the dibromo monomer and the weaker donor or acceptor aromatic is used as diboronic acid (ester) monomer. The pinacol boronate moieties at both ends of the obtained poly( p ‐phenylene) (PPP) can be converted to benzoic acid ester, hydroxyl group, and bromine. Furthermore, the reaction of the pinacol boronate‐terminated PPP with poly(3‐hexylthiophene) (P3HT) having bromine at one end yields a triblock copolymer of P3HT‐ b ‐PPP‐ b ‐P3HT. Abstract : Suzuki–Miyaura coupling polymerization of dibromoarene and arylenediboronic acid (ester) with t ‐Bu3 PPd(0) precatalyst, which has a high propensity for intramolecular catalyst transfer on the π‐face, yields high‐molecular‐weight π‐conjugated polymers with boronic acid (ester) moieties at both ends, even in the presence of excess dibromoarene. This unstoichiometric polycondensation behavior is accounted for by intramolecular transfer of the Pd catalyst on dibromoarene.